Analisis Kajian Fear of Missing Out (FoMO) dan Sales Promotion Terhadap Impulse Buying Produk Fast-Moving Consumer Goods (FMCG) - Charlotte; Endang Kustami; Dhevi Dadi Kusumaningtyas; Edwin Zusrony (ITB AAS Indonesia Surakarta, 2026)
The study aims to determine the influence of FoMO (FoMo) and sales promotions on purchasing decisions for Mie Gacoan. The population in this study was all consumers who have purchased Fast-Moving Consumer Goods (FMCG) products in Semarang Regency. The sampling technique used non-random sampling with a purposive sampling method with 60 respondents. In data collection, a questionnaire was used with an assessment parameter instrument using a Likert scale of 1-5 and was tested for validity and reliability. In data analysis, a multiple linear regression technique was used and the data was processed with the SmartPLS application version 4.1.1.4. The results of this study in partial and simultaneous tests illustrate that the impact of FoMO and sales promotions significantly and positively influences purchasing decisions for FMCG products. This research is expected to be useful for potential consumers and become a basis for purchasing decisions on FMCG products that are formed by many independent variables that influence the dependent variable.